A Jocic-type approach for a practical and scalable synthesis of pyrrolonaphthoxazepine (PNOX)-based potent proapoptotic agents - Zisterer, Daniela; Federico, Stefano; Khan, Tuhina; Relitti, Nicola; Chemi, Giulia; Brindisi, Margherita; Brogi, Simone; Novellino, Ettore; Campiani, Giuseppe; Gemma, Sandra; Butini, Stefania (My University, 2018)
We developed a Jocic-type protocol for the construction of the pyrrolonaphthoxazepine (PNOX) core. After an initial investigation based on the isolation of a trichloromethyl carbinol derivative, we shifted our attention towards a multicomponent single-step protocol. Screening of a variety of bases and solvents led to the identification of the optimum conditions for the preparation of the key a-aryloxy carboxylic acids to undergo intramolecular cyclization. The novel chemical route significantly improved overall yields for the preparation of PNOX-based compounds and was successfully extended to the preparation of 1,4-benzoxazinone-based templates.
ACCEPTED
Keywords: Pyrrolonaphthoxazepines; apoptosis; heterocycles; anti-tumour; Cancer